Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$ \frac{\partial u }{\partial t} + c \frac{\partial u}{\partial x}=e^{2x} $$ $$ -\infty < x < \infty , t>0, c>0 $$ initial value $u(x,0) = f(x), -\infty< x < \infty$


I've got the result but it's not satisfy the equation when I substitute it.

characteristic equation

$\frac{dt}{ds} = 1 \implies t = s + t_0,$ let $t(0) = 0 ,$ then $t = s$

$\frac{dx}{ds} = c \implies x = cs + x_0 = ct + x_0$

$\frac{du}{ds} = e^{2x} \implies u = s e^{2x} + u_0 = t e^{2x} + u_0$

$u_0 = u \left(x(0),0 \right) = f(x_0) = f(x-ct) $

so, $ u = t e^{2x} + f(x-ct) $

is it correct?

share|improve this question
    
is it really works? what do you mean by not a fully general solution? –  chihiroasleaf Feb 20 '13 at 14:54
    
If I substitute the result, I get $u_x = 2te^{2x} + f'(x-ct)$ and $u_t = e^{2x} - c f'(x-ct)$ so $u_t + cu_x \neq e^{2x}$ –  chihiroasleaf Feb 20 '13 at 15:04
    
This question has been solved perfectly. Hope that the asker has been diving enough and accept the answer at an early date. –  doraemonpaul Apr 21 '13 at 1:26
add comment

1 Answer

Your procedure is not corrct, so you should follow the follwing procedure:

$\dfrac{dt}{ds}=1$ , letting $t(0)=0$ , we have $t=s$

$\dfrac{dx}{ds}=c$ , letting $x(0)=x_0$ , we have $x=cs+x_0=ct+x_0$

$\dfrac{du}{ds}=e^{2x}=e^{2cs+2x_0}$ , letting $u(0)=f(x_0)$ , we have $u(x,t)=\dfrac{e^{2cs+2x_0}-e^{2x_0}}{2c}+f(x_0)=\dfrac{e^{2x}-e^{2x-2ct}}{2c}+f(x-ct)$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.